PENGARUH BUDAYA ORGANISASI, PERILAKU KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI KARYAWAN PT PEMBANGUNAN PERUMAHAN (Persero) - Sundari Soekotjo (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2015)
The study aims to find out the effect of organizational culture, leadership behavior, and job satisfaction on the commitment of the employee organization of PT Pembangunan Perumahan (Persero). A survey was conducted with a rondomly selected sample of 98 employees, with all the variables put into a correlation matrix, the data was then analysed with the path technique. The result showed that: (1) organizational culture had a direct effect on the employee’s job satisfaction; (2) organizational culture had a direct effect on the commitment of the employee organization; (3) leadership behavior had a direct effect on the employee’s job satisfaction; (4) leadership behavior had a direct effect on the commitment of the employee organization; (5) job satisfaction had a direct effect on the commitment of the employee organization; (6) organizational culture had an indirect effect on the commitment of the employee organization through job satisfaction; and (7) leadership bahavior had an indirect effect on the commitment of the employee organization througgh job satisfaction. The results suggest that organizationan culture, leadership behavior are important determinants of the employee organization’s commitment.